Dimensionamento e análise de desempenho de bombas axiais - RAMALHO, Rodolfo Vitorino Correia (2022)
A study is presented on the minimum pressure coefficient criterion on the suction side of the rotor blades for cascade geometry sections, aiming the design optimization of axial flow pumps for a recirculating water channel. This criterion was tested experimentally, in fans and pumps, and numerically in turbines, and proved to be suitable to define the initial geometry of project. The main geometric aspects of the pumps were defined through statistical correlations available in the literature. In conjunction with X-Foil software, for two-dimensional flow analysis using the panel method a computational code in MATLAB is used to automate the design process through the SolidWorks software. The analysis of the geometries is carried out using software Ansys – CFX, specific for numeric 3-D flow solution.